Learning organisations and research on Turkish engineers learning opportunities - Akgün, Mete Sinan (My University, 1996)
unknown
Keywords: Endüstri mühendisliği; Genel yönetim; Mühendislik_Öğrenim ve öğretim; Personel yönetimi